KEGIATAN SOSIALISASI STUNTING DI DAERAH PUDE’E KELURAHAN LOMPOE, KECAMATAN BACUKIKI KOTA PAREPARE - Sahida, Iis; Muin, Herlina; Albab, Muhammad Ulul; Ramadhani, Sri; Rustan, Dwi Ekawati; Muhammad, Fajriani; Rahman, Rahman; Agustina, Agustina; Chasrullah, Chasrullah; Ismira, Muh. Adnan (Batara Wisnu : Indonesian Journal of Community Services, 2021)
Stunting is defined as a height-for-age index (TB/U) less than the 3rd percentile. Posko 14, through the KKN, took the initiative to carry out stunting socialization to increase public knowledge about stunting. They were implementing stunting socialization in the midst of the COVID-19 pandemic through 3 stages, preparation of facilities and infrastructure, socialization, and evaluation stages. The implementation of stunting socialization increased the knowledge of the Pude’e community, Lompoc Village, Bacukiki District, Parepare City after being given counseling